Maternal Effects on Seed and Seedling Phenotypes in Reciprocal F1 Hybrids of the Common Bean (Phaseolus vulgaris L.) - Singh, Jugpreet; Clavijo Michelangeli, Jose A.; Gezan, Salvador A.; Lee, Hyungwon; Vallejos, C. Eduardo (Frontiers in Plant Science, 2017)
Maternal control of seed size in the common bean provides an opportunity to study genotype-independent seed weight effects on early seedling growth and development. We set out to test the hypothesis that the early heterotrophic growth of bean seedlings is determined by both the relative amount of cotyledon storage reserves and the genotype of the seedling, provided the hybrid genotype could be fully expressed in the seedlings. The hypothesis was tested via comparison of seed weight and seedling growth phenotypes of small-seeded (wild, ~0.10 g) and large-seeded (landrace, ~0.55 g) parents and their reciprocal F1 hybrids. Akaike’s Information Criteria were used to estimate growth parameters and identify the phenotypic model that best represented the data. The analysis presented here indicates that the hybrid embryo genotype is not fully expressed during both seed and seedling growth and development. The analysis presented here shows that seed growth and development are controlled by the sporophyte. The strong similarity in seed size and shape of the reciprocal hybrid seed with seeds of the maternal parents is evidence of this control. The analysis also indicates that since the maternal sporophyte controls seed size and therefore the amount of cotyledon reserves, the maternal sporophyte indirectly controls early seedling growth because the cotyledons are the primary nutrient source during heterotrophic growth. The most interesting and surprising results indicated that the maternal effects extended to the root architecture of the reciprocal hybrid seedlings. This phenomenon could not be explained by seed size, but by alterations in the control of the pattern of gene expression of the seedling, which apparently was set by a maternally controlled mechanism. Although seed weight increase was the main target of bean domestication, it also had positive repercussions on early-growth traits and stand establishment.